The Impact of Financial Literacy, Emotional Intelligence, and Peer Conformity through Money Attitudes on Consumptive Behavior (Journal of Economic Education, 2022)
This research examines students' consumptive behavior by presenting money attitude as an intervening variable mediated by the relationship between financial literacy and the purpose of emotional intelligence and peer conformity. In addition, ten hypotheses were proposed to ascertain whether the independent variables of financial literacy directly influence each other, emotional intelligence, and peer conformity, through the intervening variable of money attitude on the dependent variable consumptive behavior. The population in the quantitative research was 340 students. A sample of 170 respondents from SMA Negeri in Semarang City was selected using the cluster proportional random sampling method. Data collection using questionnaires, analysis of descriptive statistical data, and path analysis. The results shows: (1) financial literacy does not have a positive and insignificant direct impact on consumptive behavior, (2) a direct effect of emotional intelligence on consumptive behavior in a negative and significant way, (3) a direct impact of peer conformity on consumptive behavior significantly positive and significant, (4) the direct impact of money attitude on consumptive behavior is positive and significant, (5) the direct impact of financial literacy on money attitude is positive and significant, (6) the direct impact of emotional intelligence on money attitude is positive and significant, ( 7) the direct impact of peer conformity on money attitude is positive and significant, (8) the direct impact of financial literacy on consumptive behavior through money attitude is positive and significant, (9) the impact of emotional intelligence on consumptive behavior through money attitude is positive and significant, (10) direct impact peer conformity on consumptive behavior through money attitude in a positive and significant way.